2018
DOI: 10.1111/edt.12443
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic dental injury incidence of unseen children

Abstract: Background/Aims There is a lack of information about the incidence of dental trauma in Turkish children with disabilities and those in detention centers. The aim of this study was to investigate the occurrence of dental trauma in two groups estimated to have high‐potential risk, young prisoners and disabled children, compared with healthy peers. Materials and methods A total of 530 children were included in the study. The participants were divided into three groups: Disability Group (n=238), Imprisoned Childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Although most studies found that the prevalence of dental trauma was higher in the case group than the control group, only two studies found that the difference was statistically significant . Other studies have shown a higher prevalence of trauma in healthy patients when compared to patients with special needs …”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Although most studies found that the prevalence of dental trauma was higher in the case group than the control group, only two studies found that the difference was statistically significant . Other studies have shown a higher prevalence of trauma in healthy patients when compared to patients with special needs …”
Section: Resultsmentioning
confidence: 93%
“…All articles were classified as case‐control studies. In the study sample representative section, some studies showed major problems for the source of sample and minor problems in sampling method . No problems in sample size were found in six studies, and some studies showed major problems in entry criteria's/exclusions …”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations